Long term investigations of flowers and leaves on mainly non-domestica plums - Surányi, D. (International Journal of Horticultural Science, 2005)
The author dealt with plum species representing different eco-geographic areas by their genetic adaptation and their hybrids, as European (P. domestica, P. italica, P. cerasifera), Asian (P. salicina, P. simonii, P. ussuriensis), American (P. americana, P. besseyi, P. munsoniana, P. tomentosa). The rootstocks of the trees examined were seedlings of C. 679 myrobalan with the exception of Laroda and Santa Rosa II, which were grown on three different stocks: seedlings of C. 174 myrobalan, C. 449 bitter almond and C. 471 sweet almond. The size of peduncle, length of pistil, stamen number per flower, relative stamen number (SN/PL) have been suitable for description and distinction of varieties. Similarly shape of leaves, length of petiole, length and width of blade helped the identification. The ratio of the dimensions of leaves, length of petiole and of leaf blade, also contributed to the distinction of European, Asian and American plum species, notwithstanding their relations with ecological conditions as well as historical, technical properties, pomological features, etc. Computed indicators (relative stamen number and shape-index of leaves) also have been useful data. Significant correlations have been found between colour of nectaries and mean values of variety-groups. The potential values of non-European varieties for purposes of commercial production could be forecasted from the point of view of quality, ecological, pomological as well as market value. It is important, however, to know the effect of the rootstock and growing site as well as their interaction, on the one hand, whereas the resistance or tolerance of the varieties as limiting factors, at least to the sharka (Plum pox) virus, Xanthomonas pruni, on the other hand (cf. Surányi & Erdős, 2004a and 2004b).